Enhancing Resilience in Canadian Military Families and Communities: A Qualitative Analysis of the Reaching In… Reaching Out and Bounce Back and Thrive! Resiliency Skills Training Programs - Mikolas, Cynthia; Winfield, Hope; Smith-MacDonald, Lorraine; Pike, Ashley; Jones, Chelsea; Lee, Melina; Griffiths, Jennifer; Perry, Ryan; Olson, David M.; Heber, Alexandra; Olson, Joanne; Sevigny, Phillip R.; et al. (Frontiers in Public Health, 2021)
Introduction: A new vision of resilience and well-being for Canadian military service members (SMs), Veterans and their families has been championed by the Canadian Armed Forces (CAF) and Veterans Affairs Canada (VAC). Operationalizing this vision, which aims to support those who serve/have served and their families as they navigate life during and post-service, requires the support of service providers (SPs). Training SPs to deliver complementary resilience-training programs Reaching In… Reaching Out (RIRO; for adults working with parents of young children) and Bounce Back and Thrive! (BBT; for parents of children aged 0–8 years of age) may support this vision. Objective: To assess the appropriateness of RIRO/BBT trainer training for SPs, and RIRO and BBT resilience-training for military populations and families. Methods: This qualitative descriptive study involved the delivery of RIRO/BBT trainer training to SPs (n = 20), followed by focus groups (n = 6) with SPs and organisational leaders (n = 4). Focus groups were recorded, and data were transcribed and thematically-analysed. Results: Several themes emerged: (1) RIRO/BBT trainer training enabled SPs to model resilience and deliver the resilience-training programs, (2) training was appropriate and adaptable for the CAF and SMs/CMFs, and (3) training could support the development of resilient communities. Discussion: RIRO/BBT trainer training and RIRO and BBT resilience-training programs use a holistic, integrated, experiential, and community approach to resilience-building and align with CAF and VAC initiatives. Once contextualised, such programs could support resilience-building in the military context.